(untitled) (Journal of Biomedical Investigation, 2007)
Academic stress involving examinations is known to induce alterations in prolactin (PRL) physiology in human subjects. in the present study, we investigated the PRE secretory response to academic exercise in 13 male medical students during regular university examinations. Blood samples were taken at 0 hour, 1 hour and 2½ hours of the exercise during morning hours, beginning at 09.00 hours. Samples were stored under -20°C until assayed. Serum PRL concentration was estimated by a solid phase enzyme-linked immunosorbent assay techniques. Mean (7: sem) serum PRL concentrations were 7.86 ± 1.55ng/ml; 19.73 ±5.72ng/ml; and 13.6542.72 ng/ml at 0 hour, 1 hour and 2’/, hours of exercise, respectively. We conclude that academic exercise induced elevation in PRL secretion but in a on[1]uniform pattern. The PRL secretory response showed two distinct patterns or phases: an exponential phase during the first 1 hour of exercise and a declining phase thereafter.